Non-monotonic concentration dependence of the electro-phoretic mobility of charged spheres in realistic salt free suspensions - Botin, Denis; Carrique-Fernández, Félix; Ruiz-Reina, Emilio; Palberg, Thomas (AIP Publishing, 2020)
Using super-heterodyne Doppler velocimetry with multiple scattering correction, we extend the optically accessible range of concen- trations in experiments on colloidal electro-kinetics. Here, we measured the electro-phoretic mobility and the DC conductivity of aqueous charged sphere suspensions covering about three orders of magnitude in particle concentrations and transmissions as low as 40%. The extended concentration range for the first time allows the demonstration of a non-monotonic concentration dependence of the mobility for a single particle species. Our observations reconcile previous experimental observations made on other species over restricted concentration ranges. We compare our results to the state-of-the-art theoretical calculations using a constant parti- cle charge and the carefully determined experimental boundary conditions as input. In particular, we consider the so-called realistic salt free conditions, i.e., we respect the release of counterions by the particles, the solvent hydrolysis, and the formation of carbonic acid from dissolved neutral CO2. We also compare our results to previous results obtained under similarly well-defined conditions. This allows identification of three distinct regions of differing density dependence. There is an ascent during the build-up of dou- ble layer overlap, which is not expected by theory, an extended plateau region in quantitative agreement with theoretical expectation based on a constant effective charge and a sudden decrease, which occurs way before the expected gradual decrease. Our observa- tions suggest a relation of the non-monotonic behavior to a decrease in particle charge, and we tentatively discuss possibly underlying mechanisms.
Keywords: Coloides; Electrophoretic mobility; Realistic salt-free systems; Concentrated colloids